UTEROTONIC USE IN THE ACTIVE MANAGEMENT OF THIRD STAGE OF LABOR (AMTSL): SYSTEMATIC REVIEW - Noviyati Rahardjo Putri; Anis Laela Megasari (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Maternal mortality rate in Indonesia has decreased from 184/100,000 live birth (LB) (2016) to 177/100,000 LB (2017), but this number is still high enough than SDGs target of 70/100,000 LB. The one of direct cause of maternal death is hemorrhage, especially postpartum hemorrhage (PPH). Causes of PPH are uterine atony, laceration of birth canal, resistant placenta and uterine inversion. PPH prevention method is Active Management of Third Stage of Labor (AMTSL). The objective of this systematic review is to analyze the use of uterotonics in AMTSL.Methods: This systematic review used the PRISMA protocol, articles taken from Google Scholar, Science Direct, and Pub Med. The time span of the research article was 2010 to 2021.Result: The results of the study describe that the use of uterotonics in single use or combination in third stage of labor can reduce the risk of PPH and shorten the time of the stage. The side effects were reported in misoprostol and methyl ergometrine than oxytocin. In addition, combination therapy with oxytocin and misoprostol can reduce the length of the third stage and the potential for a decrease in hemoglobin within 24 hours of delivery. In Indonesia, if oxytocin is not available, maternal nipple stimulation is performed as nonpharmacological therapy or ergometrine 0.2 mg is given to patients without complications of high blood pressure.Conclusion: The use of uterotonics is adjusted to its cost-effectiveness, ability to store and refrigerate also the benefits compare to the side effects to the patients.